The Adaptation Paradox Beyond NEETUG Scores: A Cross-sectional Study of Post-admission Adaptation and Academic Performance among Medical Undergraduates in North India - Neeraj Raizada; Mudit Sharma; Monika Gupta; Vishal Bankwar; Shubham Sharma (JOURNAL OF CLINICAL AND DIAGNOSTIC RESEARCH, 2026)
Introduction: National Eligibility-cum-Entrance Test for Undergraduates (NEET-UG) score provides an entry-level marker of academic preparedness for Bachelor of Medicine and Bachelor of Surgery (MBBS) students, but academic performance after admission may also depend on study behaviour, peer context and self-regulation within the medical-college environment. Aim: To assess factors associated with satisfactory academic performance among MBBS students, with particular focus on NEET-UG category, study pattern, academic peer orientation and peer-related academic resilience. Materials and Methods: This cross-sectional study was conducted among 358 MBBS students from second year onward at the Department of Community Medicine, Jaipur National University Institute of Medical Sciences and Research Centre, Jaipur, Rajasthan, India between January 2025 and March 2025. Data were collected using an anonymous, structured, self-administered online questionnaire assessing NEET-UG category, most recent university examination performance, study pattern, residence, alcohol/smoking status, psychological distress indicators, academic peer orientation and peer-related academic resilience. Satisfactory academic performance was defined as a self-reported score of ≥60% in the most recent university examination. Associations were assessed using a Chisquare test and multivariable logistic regression. Adjusted Odds Ratios (aOR) with 95% Confidence Intervals (CI) were reported. Results: Overall, 243 students (67.9%) reported satisfactory academic performance. On adjusted analysis, NEET-UG category, gender, study pattern and peer-related academic resilience remained independently associated with satisfactory performance. Compared with the